Antimicrobial activity of different concentrations of NaOCl and chlorhexidine using a contact test - Sassone Luciana Moura; Fidel Rivail Antonio Sergio; Fidel Sandra Rivera; Dias Marina; Hirata Junior Raphael (Fundação Odontológica de Ribeirão Preto, 2003)
The purpose of this study was to analyze the in vitro antimicrobial activity of sodium hypochlorite (1% and 5%) and chlorhexidine (0.12%, 0.5% and 1%). Bacterial samples (ATCC) of Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Porphyromonas gingivalis and Fusobacterium nucleatum were submitted to a contact test. Solutions were evaluated at different time intervals: immediately, 5 min, 15 min, and 30 min after contact and repeated 10 times. The results of the contact test showed that 0.12% chlorhexidine did not eliminate E. faecalis at any time interval, while 0.5% and 1% chlorhexidine and 1% and 5% sodium hypochlorite did. These results permit us to conclude that to obtain better antimicrobial activity, chlorhexidine in a concentration greater than 0.12% should be used.